THE ROLE OF PROINFLAMMATORY CYTOKINES INTERLEUKIN 1-Β AND TUMOR NECROSIS FACTOR-Α IN DIAGNOSTICS OF PUBERTAL MENORRHAGES AGAINST THYROID PATHOLOGY - Ю. Цисар; О. Андрієць; А. Андрієць; А. Семеняк (Bukovynian State Medical University, 2023)
Introduction. During puberty, the reproductive system is vulnerable to the influence of any adverse factors that lead to a disorder of its functional state and to menstrual disorders in particular. Among the numerous factors that provoke menstrual dysfunction is the pathology of the thyroid gland. Cytokines are known to be involved in all aspects of innate and acquired immunity, including the activation of growth and differentiation of immunocompetent cells, inflammation and restoration of the function of the affected organ. Cytokines are characterized by the action of preventing the interaction of cells of the immune, hematopoietic, endocrine and nervous systems. Cytokines of the first generation are conditionally distinguished, which are produced by cells of nonspecific anti-infective protection. The main pro-inflammatory cytokines are IL-1β, IL-2, IL-6, interferons, TNF-α and others. The main factor of inflammatory reactions is multifunctional IL-1β. Tumor necrosis factor-alpha (TNF-α) is a pro-inflammatory cytokine, one of the central regulators of factors and mechanisms of innate resistance. It has many biogenic effects, most of which are similar to the action of IL-1β. Considering the above exactly IL-1β and TNF-α to study their concentration in the blood of adolescent girls with pubertal menorrhagia has been the basis of immunological studies. The aim of the study. Assessment of cytokine status in girls of pubertal age against the background of concomitant thyroid pathology. Material and methods. We examined 70 adolescent girls with pubertal menorrhagia who were treated in the gynecological department of the Chernivtsi Regional Perinatal Center. The girls were divided into two groups: I (main) included 30 adolescent girls diagnosed with pubertal menorrhagia on the background of concomitant thyroid pathology, II group (comparison) - 40 adolescent girls diagnosed with pubertal menorrhagia. Control group III - 25 practically healthy adolescent girls. Pro-inflammatory cytokines, namely interleukin 1-beta (IL-1β) and tumor necrosis factor-alpha (TNF-α) were studied once, after inclusion of patients in the study, by enzyme-linked immunosorbent assay based on a solid-phase 'sandwich' variant using mono- and polyclonal antibodies to IL-1β and TNF-α. The tubes with the serum samples were closed with lids and stored in the freezer until analysis at -20 °C. Statistical processing of the material was carried out using the computer program STATISTICA and Microsoft Exel Windows, StatSoft® Inc. The design of the study and all methods used in this study were reviewed and approved by the Bioethics Committee of the Higher Educational Institution "Bukovinian State Medical University" (protocol No. 1, dated 24.01.2011). Research work "Prevention, diagnostics and treatment of perinatal and reproductive system disorders of women and adolescent girls" (№ 201110Н state registration number 0111U006499. Term of realization: 02.2011-12.2015.) Results of the study. The obtained results of the study of the cytokine cascade showed that upon admission to inpatient treatment and examination in the blood of adolescent girls with pubertal menorrhagia without concomitant pathology, the concentration of IL-β increases significantly (by 60.61%) and a tendency to increase (4.09 times) the concentration of TNF-α in the peripheral blood of the examined patients is formed. However, the results of clinical and laboratory examinations obtained during admission for inpatient examination and treatment of adolescent girls with pubertal menorrhagia associated with thyroid pathology showed that patients have a steady tendency to decrease the concentration of IL-1β by 6.96% and TNF-α - by 1.48 times. It was found that the pathology of the thyroid gland contributes to the inhibition of immunocompetent cells production of IL-1β by 1.66 times, TNF-α by 6.04 times. Conclusion. Pathology of the thyroid gland leads to a decrease in immunoregulatory function due to a decrease in the concentration of some important proinflammatory cytokines (IL-1β and TNF-α).